Examining Academic Fraud in Economics Courses: Insights from The Fraud Pentagon at Muhammadiyah 5 Gatak High School - Sholihah, Destian Anggita Putri; Jatmika, Surya (Proceedings International Conference on Education Innovation and Social Science, 2024)
The objective of this research is to describe academic fraud in the economics subject at Muhammadiyah 5 Gatak High School and to identify the factors causing academic fraud in the economics subject at Muhammadiyah 5 Gatak High School through the dimensions of the fraud pentagon. This study uses a qualitative approach with a case study research design. The subjects of this research are two economics teachers and five eleventh-grade social science students. Data collection was carried out through interviews and documentation. The data analysis techniques used in this study are data condensation, data display, and conclusion drawing. The results of this research indicate that (1) The forms of academic fraud commonly committed by eleventh-grade social science students in the economics subject include cheating, and collaborating on assignments or exams. (2) The reasons students commit academic fraud in the economics subject include difficulty in understanding the material and laziness to study, pressure on students to achieve high grades, unpreparedness in completing assignments/exams, opportunities to commit academic fraud in the economics subject due to the difficult-to-understand material and lack of supervision, and the low academic abilities of students leading them to commit fraud.